Upgrading of TPST 3R Mulyoagung Bersatu Performance Based On Health Protocol In The New Normal Era - Achmad Bambang Barrul Fuad; Iqbal Ramadhani Fuadiputra; Luqman Dzul Hilmi (Jurnal Dedikasi, 2021)
Global warming that occurs, one of which can not be separated from the garbage that is thrown away by people carelessly and they are not fully aware of the dangers of the waste. Even though the waste has been disposed of in its place, then transported by the cleaning staff to the Final Disposal Site and without any follow-up handling it will also be dangerous. Examples of organic waste that mixes with the environment such as in the soil, then decomposes will cause methane gas which can thicken the layer of the greenhouse effect. Then what about non-organic waste, such as plastic, rubber, yarn, to metal, which also have a very polluting impact on the environment. Therefore, it is necessary to follow up the handling of waste, especially household waste (SRT) in the community. The service team this time used a bottom up system to solve partner problems. In addition to using the system, the canvas business is also used as a solution to solve this problem. The results of the service show that with the implementation of the health protocol, the economic activities carried out by partners gradually improve and can run with strict and regular protocols.